Eliciting metaphors from narratives of collaboration experiences with teachers in writing a textbook - Jarjani Usman; Mawardi Mawardi (Studies in English Language and Education, 2022)
Collaboration of teacher educators with school teachers in developing lesson materials is paramount for professional development. A burgeoning of research on educator-teacher collaboration in writing a textbook, for instance, has existed; however, there is little attention to the narratives on the collaborators’ experiences through the metaphorical lens. Telling stories about collaborative experiences through the metaphorical lens can help understand the complexity of phenomena because thoughts are implicit and difficult to express. This study attempted to fill the void by analyzing the experiences of partnering with English teachers in developing the textbook of classroom action research (CAR). It involved stories of the researchers upon their collaborative writing experiences working with twelve primary school teachers in Aceh, Indonesia. In analyzing the collaborators’ experiences, this study drew upon Lakoff and Johnson’s Conceptual Metaphor Theory (CMT). Analyses of the collaborators’ stories upon their experiences generated four primary implicit metaphors that represent acquisition metaphors rather than participation metaphors, such as ‘collaborative writing is listening to the trainers’, ‘collaborating teachers as the trainees’, ‘university collaborators as the experts’, and ‘product is more important than the process’. The findings offer insights into the importance of reflecting on the experiences and generating metaphors to make sense of roles played by collaborating teachers and lecturers involved in a collaborative project.